Novel chiral metasurface design with ring resonators for THz applications - Mohamed, Heba G.; Kilius, Sarunas; Zakaria, Rozalina; Soto-Diaz, Roosvel; Escorcia-Gutierrez, José; Andriukaitis, Darius (Frontiers in Physics, 2025)
IntroductionAs an artificial two-dimensional material, metasurfaces are essential for modifying the fundamental characteristics of electromagnetic (EM) waves. Numerous researchers have created and validated metasurface uses, including anomalous reflection, polarization rotation, and absorption. The development of chiral metasurfaces that exhibit spin-selective transmission or reflection offers a novel method of manipulating circularly polarized (CP) waves. Because of their enormous chiroptical responses, which are orders of magnitude larger than those of natural chiral materials, chiral metasurfaces have also garnered a lot of interest in the field of spin photonics.MethodsThis paper proposes a novel chiral metasurface for dual-band THz circularly polarized anomalous reflecting and absorbing. The co-polarized reflection for incident right-handed and lefthanded circularly polarized waves is achieved via the metasurface structure, which is made up of two chiral structures. The corresponding absorption rates are 96.3% and 90.9%, respectively. The full 360° coverage is realized by rotating the chiral metasurface unit using Pancharatnam-Berry phase principle.Results and DiscussionSimulation results show that the proposed metasurface has multi-function beam control capability and can be deployed in chiral sensing, electromagnetic energy harvesting, polarization converters, radar and other applications.